Analisis Perbandingan Model Kesulitan Keuangan Studi Pada Bank Bukopin Tbk - Kawulur, Hisky Ryan (E-Jurnal Akuntansi; Vol 31 No 6 (2021)DO - 10.24843/EJA.2021.v31.i06.p15, 2021)
The purpose of this study is to analyze and compare the predictive value of the Altman z-score model of financial distress with the Zmijewski model. The research method used is descriptive quantitative in explaining the phenomena that occur. This study uses data from Bukopin's financial statements for 2018, 2019 and 2020. Data analysis is carried out by calculating the ratio of each model from 2018, 2019 and 2020, then the results of the criteria from the altman z-score model and the zmijewski model are compared and analyzed according to the criteria. The results showed that both the Altman z-score model and the Zmijewski model gave the same results, namely in the years to come the company has the potential to face bankruptcy. Keywords: Altman Z-Score; Zmijewski; Banking; Comparison Model.